Application of solvent-assisted dispersive solid phase extraction as a new, fast, simple and reliable preconcentration and trace detection of lead and cadmium ions in fruit and water samples. (15th November 2015) - Behbahani, Mohammad; Ghareh Hassanlou, Parmoon; Amini, Mostafa M.; Omidi, Fariborz; Esrafili, Ali; Farzadkia, Mehdi; Bagheri, Akbar
Highlights: Sensitive flame atomic absorption spectrophotometry determination of cadmium and lead. Solvent assisted dispersive solid phase extraction. Good detection limit and repeatability. Low cost and environmentally friendly. Abstract: In this research, a new sample treatment technique termed solvent-assisted dispersive solid phase extraction (SA-DSPE) was developed. The new method was based on the dispersion of the sorbent into the sample to maximize the contact surface. In this approach, the dispersion of the sorbent at a very low milligram level was achieved by injecting a mixture solution of the sorbent and disperser solvent into the aqueous sample. Thereby, a cloudy solution formed. The cloudy solution resulted from the dispersion of the fine particles of the sorbent in the bulk aqueous sample. After extraction, the cloudy solution was centrifuged and the enriched analytes in the sediment phase dissolved in ethanol and determined by flame atomic absorption spectrophotometer. Under the optimized conditions, the detection limit for lead and cadmium ions was 1.2 μg L −1 and 0.2 μg L −1, respectively. Furthermore, the preconcentration factor was 299.3 and 137.1 for cadmium and lead ions, respectively. SA-DSPE was successfully applied for trace determination of lead and cadmium in fruit ( Citrus limetta, Kiwi and pomegranate) and water samples. Finally, the introduced sample preparation method can be used as a simple, rapid, reliable, selective and sensitive method for flame atomic absorption spectrophotometric determination of trace levels of lead and cadmium ions in fruit and water samples.